Effect of intra-arrest transport, extracorporeal cardiopulmonary resuscitation and immediate invasive assessment in refractory out-of-hospital cardiac arrest: a long-term follow-up of the Prague OHCA trial - Rob, Daniel; Farkasovska, Klaudia; Kreckova, Marketa; Smid, Ondrej; Kavalkova, Petra; Macoun, Jaromir; Huptych, Michal; Havrankova, Petra; Gallo, Juraj; Pudil, Jan; Dusik, Milan; Havranek, Stepan; et al. (Critical care (London, England), 2024)
BACKGROUND: Randomized data evaluating the impact of the extracorporeal cardiopulmonary resuscitation (ECPR) approach on long-term clinical outcomes in patients with refractory out-of-hospital cardiac arrest (OHCA) are lacking. The objective of this follow-up study was to assess the long-term clinical outcomes of the ECPR-based versus CCPR approach. METHODS: The Prague OHCA trial was a single-center, randomized, open-label trial. Patients with witnessed refractory OHCA of presumed cardiac origin, without return of spontaneous circulation, were randomized during ongoing resuscitation on scene to conventional CPR (CCPR) or an ECPR-based approach (intra-arrest transport, ECPR if ROSC is not achieved prehospital and immediate invasive assessment). RESULTS: From March 2013 to October 2020, 264 patients were randomized during ongoing resuscitation on scene, and 256 patients were enrolled. Long-term follow-up was performed 5.3 (interquartile range 3.8-7.2) years after initial randomization and was completed in 255 of 256 patients (99.6%). In total, 34/123 (27.6%) patients in the ECPR-based group and 26/132 (19.7%) in the CCPR group were alive (log-rank P = 0.01). There were no significant differences between the treatment groups in the neurological outcome, survival after hospital discharge, risk of hospitalization, major cardiovascular events and quality of life. Of long-term survivors, 1/34 (2.9%) in the ECPR-based arm and 1/26 (3.8%) in the CCPR arm had poor neurological outcome (both patients had a cerebral performance category score of 3). CONCLUSIONS: Among patients with refractory OHCA, the ECPR-based approach significantly improved long-term survival. There were no differences in the neurological outcome, major cardiovascular events and quality of life between the groups, but the trial was possibly underpowered to detect a clinically relevant difference in these outcomes. Trial registration ClinicalTrials.gov Identifier: NCT01511666, Registered 19 January 2012.
Keywords: kardiopulmonální resuscitace; Extracorporeal cardiopulmonary resuscitation; Out-of-Hospital Cardiac Arrest; kvalita života; retrospektivní studie; Quality of Life; zástava srdce mimo nemocnici; následné studie; Out-of-hospital cardiac arrest; Quality of life; Follow-Up Studies; Time Factors; lidé; Cardiopulmonary Resuscitation; Humans; časové faktory; Long-term; Retrospective Studies; Extracorporeal membrane oxygenation